The Acentropinae and Musotiminae (Lepidoptera, Pyralidae) of the Galapagos Islands, Ecuador - Landry, Bernard; Roque-Albelo, Lazaro (Zootaxa, 2006)
The Acentropinae and Musotiminae (Lepidoptera, Pyralidae) are recorded for the Galapagos Islands, Ecuador for the first time. They are represented by one species each: Parapoynx fluctuosalis (Zeller, 1852) and Undulambia lindbladi Landry n. sp., respectively. The latter has been reared from the fern Pteridium aquilinum var. arachnoideum Herter (Polypodiaceae).